(untitled) (BIRDEM Medical Journal, 2017)
Background: Medical waste can be generated in hospitals or clinics where diagnosis and treatment are conducted. The management of these wastes are of public concern and health threats are associated with such wastes. The study assessed to explore the current situation of medical waste management and level of awareness related to impact of medical waste and its management among the different levels of professionals. Methods: A descriptive cross-sectional study was done and data were collected from September 2012 to December 2012 at BIRDEM General Hospital. Data were collected by simple random sampling method and semi-structured questionnaire were used in this study. The questionnaire included socio-demographic information, source of hospital waste, description of hospital waste, segregation of waste and assessment of medical waste management system. The questionnaires were interviewed to the doctors, nurses, paramedical staff and cleaners who were related to waste management practices. Results: A total of 186 participants were interviewed in this study. The mean and SD of age was 37.9 ± 10.4 years and the age range from 22 to 65 years respectively. The male and female subjects were 28.0% and 72.0% respectively. Of the total participants, doctors, nurses, paramedical staff and cleaners were 15.1%, 55.4%, 12.9% and 16.7% respectively. To assess the perception of the respondents about hospital waste management, the nurses (100.0%) and cleaners (100.0%) were found in a better position to follow color-coding system (CCS) and to use of protective bags while segregating primary waste, while doctors (21.4%) and paramedical staff’s (29.2%) practice were not encouraging. However, in terms of constituents of medical waste doctors and paramedical staff’s perception was better than the nurses and cleaners. Doctors (92.9%), nurses (96.1%) and paramedical staff (95.8%) were very comfortable about the present color coding system than compared with cleaners (74.2%), although the doctors are less compliant to follow the color-coding system (78.6% compliant) in practice. A substantial proportion of the doctors (71.4%) sometimes put waste in wrong bins as opposed to 51.5% nurses and 33.3% paramedical staff. Few of the respondents would consider the waste if some medical waste is accidentally put to the general waste bin, 85.7% of the doctors, 95.1% nurses, 66.7% paramedical staff and 100% cleaners told that they would consider the waste as medical waste. Nurse’s perception was also better compared to other occupants in sealing waste-bin for disposal. In view of improving the existing waste management system, most of the respondents of different categories were in favor on waste management system. Majority of the respondents think that there should be designated person (97.8%) or rules (97.8%) or monitoring (96.8%) at the administrative level for organizing and managing of waste collection, handling, storage and disposal of waste who will follow a definite rule during all these processes. Conclusion: The study observed that there is lack of knowledge affiliate and practice among the doctors, nurses, paramedical staff and cleaners in segregating hospital waste at the primary source of collection. However, nurses and cleaners were more aware than the doctors and paramedical staff in terms of practice of segregating primary waste. The study also found that perception of waste management was better in doctors and paramedical staff than compared with cleaners and other staffs. To improve the waste management system, it is needed to make policy and regulation guidelines to well-organized system of collecting and treating waste in the hospital. Birdem Med J 2018; 8(1): 56-62